2020
DOI: 10.3389/fnagi.2020.586233
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Parkinson’s Disease Patients With Syntactic and Socio-emotional Verbal Measures

Abstract: Frontostriatal disorders, such as Parkinson’s disease (PD), are characterized by progressive disruption of cortico-subcortical dopaminergic loops involved in diverse higher-order domains, including language. Indeed, syntactic and emotional language tasks have emerged as potential biomarkers of frontostriatal disturbances. However, relevant studies and models have typically considered these linguistic dimensions in isolation, overlooking the potential advantages of targeting multidimensional markers. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…As previously reported 48 , 51 54 , envy- and Schadenfreude -eliciting situations of the task consistently produce higher ‘displeasure’ and ‘pleasure’ ratings than neutral scenarios. Furthermore, a validation study confirmed that said situations were specific in evoking envy and Schadenfreude compared to other socio-moral emotions such as pride and guilt 50 .…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…As previously reported 48 , 51 54 , envy- and Schadenfreude -eliciting situations of the task consistently produce higher ‘displeasure’ and ‘pleasure’ ratings than neutral scenarios. Furthermore, a validation study confirmed that said situations were specific in evoking envy and Schadenfreude compared to other socio-moral emotions such as pride and guilt 50 .…”
Section: Methodssupporting
confidence: 79%
“…Furthermore, a validation study confirmed that said situations were specific in evoking envy and Schadenfreude compared to other socio-moral emotions such as pride and guilt 50 . The task has been employed in samples of older adults from Latin America 50 , 51 , successfully evoking envy and Schadenfreude 50 , 51 , and capturing its canonical neuroanatomical basis 50 (i.e., the anterior cingulate cortex for envy 34 and the striatum and posterior regions for Schadenfreude 34 , 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…The use of naturalistic, contextual and ecological approaches to embodied language (Birba, Beltrán, et al, 2020;Birba, Vitale, et al, 2020;García et al, 2020;Trevisan et al, 2017) seem to be a powerful tool to identify selective deficits in neurodegeneration and other brain diseases (Baez et al, 2020;Calvo et al, 2019;Díaz-Rivera et al, 2022;Eyigoz et al, 2020;García et al, 2018;Moguilner et al, 2021;Suárez-García et al, 2021). Interoceptive deficits and their relation with contextual modulation is also an innovative embodied approach across brain diseases (Abrevaya et al, 2020;Birba et al, 2022;de la Fuente et al, 2019;Fittipaldi et al, 2020;García-Cordero et al, 2016;Gonzalez Campo et al, 2020;Salamone et al, 2021;Yoris et al, 2020).…”
Section: From Normal Aging To Neurodegenerative Diseases and Brain Da...mentioning
confidence: 99%
“…Finally, patients were tested in the on phase of medication, creating maximally stringent conditions for our hypotheses. Still, dopamine bioavailability can modulate speech outcomes (as captured via automated tools) 23 and other communicative skills 111,112 in PD. Some of the variables targeted herein could also be influenced by medication status, inviting further research.…”
Section: Limitations and Further Researchmentioning
confidence: 99%